Survei Minat Belajar PJOK Siswa SMP Negeri 2 Megaluh - Wibowo, Bagus Setya; Basuki; Hamid, Faisol; Prasetyo, Rahayu (SPRINTER: Jurnal Ilmu Olahraga, 2025)
This study was conducted to determine students' learning interests in physical education, sports, and health subjects at SMP Negeri 2 Megaluh. This study is a descriptive quantitative study with a survey approach. This study used a questionnaire as a data collection tool. The study was conducted at SMP Negeri 2 Megaluh. The population in this study were students of class VIII of SMP Negeri 2 Megaluh. The sampling technique in this study was simple random sampling. The sample in this study was students of class VIII-C as the research class. Based on the results of data analysis, students' interest in learning PJOK at SMP Negeri 2 Megaluh is in the very high category. It can be seen that for internal factors, the attention indicator is 94.68%. The feeling of happiness indicator has a percentage of 96.09% in the very high category. The activity indicator has a percentage of 96.71% in the very high category. While for external factors, the school indicator has a percentage of 95.70% in the very high category and the environmental indicator has a percentage of 98.17% in the very high category. So it can be concluded that students' interest in learning the Physical Education subject of SMP Negeri 2 Megaluh is very high, which can be influenced by intrinsic factors such as attention, feelings of pleasure, and activity as well as extrinsic factors such as school and environment.